The degree of the need for managers working in the directories of education to develop their skills for the exercise of administrative empowerment - مي فيصل احمد سلام عبد الجليل الخفاجي جمعة الكبيسي (College of Education for Women, 2019)
A field study investigated the degree of need for managers working in the directories of education to develop their skills for the exercise of administrative empowerment, and it adopted the descriptive analytical approach. The research community, was determined which consisted of 126 principals, and the sample was selected with arte of randomly Statistics and by (100%) of the research community, as the number of respondents was (126) of managers working in the directories of education. A questionnaire was built which included 40 items distributed among the fields of study. Researchers verified its validity and reliability. The research data were analyzed using software (SPSS), the questionnaire was applied in the second semester of the academic year 2015-2016. And come to the most important results: a great need among a sample research to develop the basic abilities that enable them to exercise administrative functions, and the research sample recognizes the importance of incentives in encouraging workers to prepare them for more practice empowerment. The research presented a number of recommendations and proposals. Keywords: the degree of need for managers in the directories of education, administrative empowerment.